Takayasu’s arteritis with dilated cardiomyopathy associated with tuberculosis: A case report - Tanti, Sanjay Kumar; Diwakar, Kumar; Mishra, Sudhir (Indian Journal of Child Health, 2020)
Takayasu arteritis (TA) is a rare, chronic inflammatory large-vessel vasculitis of unknown etiology. A possible relationship between TA and tuberculosis (TB) has been suggested. Both the diseases show similar chronic inflammatory lesions (granulomas) on the arterial walls. Although TA may have various presentations, it presents rarely as dilated cardiomyopathy (DCM). We hereby report a case of TA with DCM, associated with TB.